ETIOLOGY AND CLINICAL STRUCTURE OF SLEEP DISORDERS IN EARLY CHILDHOOD ONTOGENESIS - Islomova , Nargiza; Zainullin , Ilfat (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
This article analyzes sleep disorders in children, their types, and causes from a scientific perspective. It details the impact of sleep on a child's physical and mental development, risk factors for sleep disturbances, and methods for their prevention. Additionally, psychological and social aspects of sleep disorders, such as learning difficulties, inability to concentrate, and behavioral issues, are examined. Research indicates that early detection of sleep disorders and the application of appropriate treatments enhance a child's healthy development and overall well-being. The article also includes recommendations for parents and educators on sleep hygiene and the promotion of a healthy lifestyle.